Uji Fitokimia dan Antibakteri Ekstrak Daun Laban Ara (Endospermum peltatum Merr.) pada Bakteri Staphylococcus epidermidis - Pujianti, Eva; Hendra, Medi; Dharma, Bodhi (BIOPROSPEK: Jurnal Ilmiah Biologi, 2016)
This study aimed to know the types of secondary metabolite compounds contained in the ethanol extract of leaves laban ara (Endospermum peltatum Merr.) and the knowing the magnitude of the antibacterial activity of ethanol extract from the leaves of the laban ara (Endospermum peltatum Merr.) the growth of bacteria Staphylococcus epidermidis. The activity was shown by clear zone surrounding. The experimental design was using Complete Randomized Design (CRD), consisting six treatments, solution concentration of 10%; 20%; 40%; 80% chloramphenicol as the (positive control) and etanol as (negative control), by using four replications. The result of this study indicate that ethanol extract of leaves laban ara (Endospermum peltatum Merr.) compounds positive flavonoid, alkaloids, triterpenoid and steroid well as tannins. From antibacterial test result has been done shows that ethanol extract of leaves laban ara have inhibitory at all levels the concentrations to be tested. At concentrations of 10% namely on average by 3,067 mm, concentrations of 20% average by 3,945 mm, concentrations of 40% average by 4,312 mm and concentrations of 80% average by 4,777 mm. These results indicated that ethanol extract of leaves laban ara showed antibacterial properties, although still below chloramphenicol.